Extractability and Chromatographic Characterization of Wheat (Triticum aestivum L.) Bran Protein. Issue 5 (8th April 2015) - De Brier, N.; Gomand, S.V.; Celus, I.; Courtin, C.M.; Brijs, K.; Delcour, J.A.
Abstract About 70% of the protein for human consumption is derived from plants, with cereals as the most important source. Wheat bran protein has a more balanced amino acid profile than that of flour. We here for the first time report the amino acid, size exclusion, and SDS‐PAGE profiles of bran Osborne protein fractions (OPFs). Moreover, we also investigated how OPFs are affected when physical barriers which entrap proteins in bran tissues are removed. Albumin/globulin is the most abundant OPF. It is richer in lysine and asparagine/aspartic acid than other OPF. Most bran albumin/globulin proteins have a molecular weight (MW) lower than 30 k and their chromatographic profiles differ from those of flour. The prolamin has high levels of proline and glutamine/glutamic acid. It is rich in proteins with a MW of 30 to 45 k and about 66 k reflecting contamination with gliadin from endosperm. The glutelin has high levels of glycine, proline, and glutamine/glutamic acid. Its protein is of intermediate and high MW with little protein with MW lower than 30 k. The high (MWs from 80 to 120 k) and low (MW around 45 k) MW glutenin subunits of flour are also present in bran. The glutelin of wheat endosperm is named glutenin. Ball milling releases albumin/globulin and glutelin but not prolamin. Not all glutelin was endosperm glutenin as a substantial part was entrapped in the aleurone cells.